1997
DOI: 10.1007/s004649900464
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopically assisted gastric surgery using Dexterity Pneumo Sleeve

Abstract: The utilization of this device resulted in a more easily performed dissection, resection, and anastomosis and was felt to decrease operation time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
20
0
1

Year Published

1999
1999
2005
2005

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(22 citation statements)
references
References 10 publications
1
20
0
1
Order By: Relevance
“…The HALS gastric bypass procedure that we developed has been described in detail elsewhere [1]. The operation is comprised of two phases.…”
Section: Surgical Techniquementioning
confidence: 99%
See 2 more Smart Citations
“…The HALS gastric bypass procedure that we developed has been described in detail elsewhere [1]. The operation is comprised of two phases.…”
Section: Surgical Techniquementioning
confidence: 99%
“…The procedure is technically demanding and complex, requiring advanced laparoscopic skills and the assistance of a capable ®rst assistant with similar skills. Hand-assisted laparoscopic (HALS) gastric procedures have been adopted by some surgeons to treat obesity because it is easier to perform than the total laparoscopic procedure [1,4,5,8]. However, to date, no study has reported on the outcomes of hand-assisted laparoscopic gastric bypass as compared to those obtained with the traditional open gastric bypass procedure.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Ibrahim et al [89] presented two cases of gastric leiomyoma that were successfully removed laparoscopically. Naitoh and Gagner [90] reported two cases of extensive laparoscopic gastric resection carried out with the assistance of a sleeve device that allows the surgeon to put his or her hand into the peritoneal cavity. Choi and Oh [91] reported their experience with 32 patients with gastric submucosal tumors, all of which were removed by the laparoscopic technique.…”
Section: Laparoscopic Gastric Surgerymentioning
confidence: 99%
“…Auch über handassistierte laparoskopische Magenresektionen wird häufig berichtet [8,9]. So beschrieben Naitoh und Gagner [10] eine Billroth-IIResektion, eine Keilresektion und einen gastralen Bypass, die erfolgreich laparoskopisch handassistiert operiert wurden. Romanelli et al [9] werteten handassistierte laparoskopische Eingriffe in den USA aus und berichten über erfolgreich ausgeführte Gastrektomien.…”
unclassified